Optimal Use of Plant Stanol Ester in the Management of Hypercholesterolemia. (12th October 2015) - Rosin, Susanna; Ojansivu, Ilkka; Kopu, Aino; Keto-Tokoi, Malin; Gylling, Helena
Abstract : Plant stanol ester is a natural compound which is used as a cholesterol-lowering ingredient in functional foods and food supplements. The safety and efficacy of plant stanol ester have been confirmed in more than 70 published clinical studies and the ingredient is a well-established and widely recommended dietary measure to reduce serum cholesterol. Daily intake of 2 g plant stanols as plant stanol ester lowers LDL-cholesterol by 10%, on average. In Europe, foods with added plant stanol ester have been on the market for 20 years, and today such products are also available in many Asian and American countries. Despite the well-documented efficacy, the full potential in cholesterol reduction may not be reached if plant stanol ester is not used according to recommendations. This review therefore concentrates on the optimal use of plant stanol ester as part of dietary management of hypercholesterolemia. For optimal cholesterol lowering aiming at a lower risk of cardiovascular disease, plant stanol ester should be used daily, in sufficient amounts, with a meal and in combination with other recommended dietary changes.